Practise, organisation and quality control of microfilming projects - Schouten, Dennis (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2003)
Nicholson Baker, his name has already been mentioned several times during this conference. In 1994 he published an erotic fantasy novel: The Fermata. I will not discuss the contents of this novel before this audience, but I want to read to you a quotation: "The particular library table I had chosen with some care, of course. It had one other resident, a petite woman in her late thirties with curly salt and pepper hair (…). She was looking through several piles of microfilm copies, sorting them and and circling paragraphs ever so often. She spun her pen silently on the table as she read, as if it was a spinner in a child’s game. Her eyes moved with impressive speed over the chemical smelling, legal sized pages, but she looked tired from spending hours gazing at the grey light in one of the libraries horrible microfilm readers, contending with the trembling magnified crotch hairs and scratches on its screen." It appears that Baker already was concerned about microfilming and reading equipment by that time. Seven years later he launched his famous campaign against libraries’ abuse of microfilming as an excuse for destroying originals, mainly newspapers and periodicals in his book Double Fold (Baker, 2001).